Bibliometric Analysis of Health Information System (HIS) Research Development in Developing Countries in Asia - Bungsu, Ade Utari; Salim, Tamara Adrian; Datang, Frans Asisi; Wibowo, Muhamad Prabu (Journal La Medihealtico, 2024)
The recent COVID-19 pandemic prompted massive collaboration in health information exchange, emphasizing the importance of knowledge and information management. Health Information Systems (HIS) are a key element in the success of health organizations. This research analyzes the bibliometric development of HIS in Developing Countries in Asia (2003-2023). HIS, the technological foundation that supports health information management, has made a significant contribution to optimizing health services. This research aims to explore research trends, institutional collaborations, and research focus in the field of HIS. The results show significant indications and trends, and have an impact on COVID-19. Core journals, institutions, and contributing researchers were identified. Co-word analysis provides an overview of the diversity of disciplines involved and specific research focuses. In conclusion, HIS research in Developing Countries reflects dynamic evolution and multidisciplinary engagement.